Work-Nonwork Spillover of Wage Justice through Work Capabilities in Low and Middle Income Workers. Issue 3 (3rd July 2019) - Ellorenco, Sarah; Teng-Calleja, Mendiola; Bertulfo, Donald Jay; Clemente, Jose Antonio; Menguito, Ma. Ligaya
Abstract: Wage justice literature asserts that it is the perceived fairness of pay (based on comparison others) instead of actual pay that matters most to an employee. This study therefore investigates the spillover effect of wage justice on life capabilities in the Philippines. It is hypothesized that wage justice will influence life capability through work capabilities such as job empowerment, job satisfaction, and occupational pride. Using data from the Institute of Philippine Culture study on living wages of 500 individuals, a structural equation model was estimated to test the spillover effect. Findings confirms the hypothesis that wage justice influences life capabilities (life satisfaction and physical well-being) through work capabilities. Implications for research on wage justice and capabilities as well as to people management practices in work organizations are discussed.